Effects of frequency and duty cycle of pulsating direct current on the electro-dewatering performance of sewage sludge. (March 2020) - Deng, Wenyi; Lai, Zhicheng; Hu, Menghao; Han, Xiaoran; Su, Yaxin
Abstract: Electro-dewatering of sewage sludge with pulsating direct current (PDC-dewatering) was conducted to investigate the effects of pulsating frequency (0.01–60 Hz) and duty cycle (DTC) (20–100%) on sludge dewatering. The results indicated that both the frequency and DTC showed marked influences on electro-dewatering. Compared with the condition under the stable direct current (SDC-dewatering) of 30 V, the filtrate discharged from PDC-dewatering (at DTC of 40–60% and frequency of 30 Hz) was about 8% higher than that from SDC-dewatering. At DTC of 40%, the sludge electro-dewatering performance was promoted when the frequency increased from 0.01 Hz to 30 Hz. Compared with SDC-dewatering, PDC-dewatering can effectively mitigate ohmic heating. Layered tests were also conducted to investigate the differences of SDC- and PDC-dewatering in the distributions of water, pH, organic matters, zeta potential and conductivity in the upper, middle and lower layer of sludge cake. The results indicated that the variation tendencies of these parameters were similar between SDC- and PDC-dewatering, but the water, organic matters and charged ions in sludge cake were more homogeneously distributed during PDC-dewatering than SDC-dewatering. In addition, the anodic pH of PDC-dewatering was higher than that of SDC-dewatering, suggesting the potential of mitigating anodic corrosion during PDC-dewatering. Finally, energy consumptions of PDC- and SDC-dewatering were calculated and compared. The effects of frequency and DTC on energy consumption were investigated. PDC-dewatering was found to be more energy efficient than that of SDC-dewatering, making PDC-dewatering a promising electro-dewatering technology in future. Graphical abstract: Image 102110 Highlights: PDC-dewatering can promote dewatering and mitigate ohmic heating simultaneously. PDC-dewatering showed the optimum performance in the DTC range of 40–60% (30 Hz). PDC-dewatering showed the potential of mitigating anodic corrosion. The charged species in sludge cake were more homogeneously distributed during PDC-dewatering than SDC-dewatering. PDC-dewatering was found to be more energy efficient than that of SDC-dewatering.